Sertifikasi Amil Zakat sebagai Instrumen Penguatan Dakwah Struktural : A Certification of Amil Zakat as an Instrument for Strengthening Structural Da‘wah - Choirin, Muhammad; Muhibbudin; Nugraha, Moch Karya; Faatihah, Yuyun Nurul; Ramadan, Imam Afriadi (Direktorat Jenderal Bimbingan Masyarakat Islam, 2025)
The professional certification program for amil zakat, initiated by the Ministryof Religious Affairs in collaboration with the Professional Certification Body(LSP) of BAZNAS RI, represents a strategic effort to strengthen Islamicphilanthropic da‘wah through enhanced professionalism and standardized competencies. This study examines how the certification program transforms the role of amils as agents of social da‘wah, and how collaboration between the state and professional institutions shapes a model for institutional strengthening within the zakat sector that affects the quality of public services. Employing a qualitative-descriptive approach and case studies conducted at three implementation sites (two in Jakarta and one in Semarang), this study finds that certification not only improves the technical capacity of amil in fundraising, management, and zakat reporting but also reinforces the public image of zakat institutions as accountable and modern entities. These findings affirm that competency standardization through amil zakat certification functions as an instrument of structural da‘wah, contributing to advancing national zakat governance and supporting the broader ecosystem of Islamic philanthropy in the development of Islamic civilization.